Optimization of the Process of Making Organic Fertilizer from Chicken Manure as a Source of Plant Nutrition by Determining the Value of Potential pH, Actual pH, Organic Material Content, and Lime Substance - Yolanda Ratnasari Hutabarat; Karen Tio Ulibasa Panjaitan; Elfayetti; Elsa Kardiana; Putra Ferdiansyah Limbong; Putri Seruni; Bunga Mandalika (PT. Intelek Cendikiawan Nusantara, 2025)
Organic fertilizer made from chicken manure is an effective solution for improving soil fertility in sustainable agriculture. This study aims to evaluate the process of producing organic fertilizer by measuring potential pH, organic matter content, and lime content. The experimental method was conducted in Dusun XV Suka Mulia, Labuhan Deli District, from February 14 to March 11, 2025. The materials used included chicken manure, sawdust, EM4 liquid, liquid brown sugar, and soil, which were fermented for 21 days. Laboratory test results showed that the produced fertilizer had high organic matter content and pH levels ranging from 6 to 7, which are ideal for plant growth. This fertilizer also contains lime, which plays an important role in balancing pH and enhancing the availability of nutrients in the soil. The study concludes that organic fertilizer from chicken manure can reduce dependence on chemical fertilizers and mitigate environmental pollution from livestock waste, making it a sustainable alternative for agriculture.